Worse overall health status negatively impacts satisfaction with breast reconstruction. Issue 11 (November 2020) - Mehta, Sumarth K.; Olawoyin, Olamide; Chouairi, Fouad; Duy, Phan Q.; Mets, Elbert J.; Gabrick, Kyle S.; Le, Nicole K.; Avraham, Tomer; Alperovich, Michael
Summary: Background: BREAST-Q is a validated measure of patient satisfaction and health-related quality of life following breast surgery. Limited evidence exists with regard to the influence of preoperative overall health status on BREAST-Q outcomes. The American Society of Anesthesiologists (ASA) physical status classification is representative of preoperative overall health and its impact on patient-reported outcomes can be assessed. Methods: Patients who received breast reconstruction at Yale New Haven Hospital between 2013 and 2018 and completed the BREAST-Q were enrolled in the study. Associations between BREAST-Q scores within modules and between modules and ASA were analyzed. Pearson's correlation and Spearman's Rho were used to characterize correlations between patient factors and BREAST-Q scores. Significantly correlated factors were entered into a general linear model (GLM) to control for confounding variables and isolate the effect of ASA on BREAST-Q scores. Results: A total of 1136 patients underwent breast reconstruction of whom 489 patients completed the BREAST-Q. Increasing ASA indicative of worsening overall health was associated with a decreased BREAST-Q score for all modules except Physical Well-being of the Abdomen ( p <0.01 to p  = 0.029). In a GLM controlling for relevant covariates, ASA remained a significant contributor for all modules except Physical Well-being of the Chest ( p <0.01 to p  = 0.021). BREAST-Q scores decreased by approximately twice as much from ASA 1 to 2 compared to ASA 2 to 3. Conclusion: ASA classification is an independent predictor of BREAST-Q patient-reported outcomes following breast reconstruction. Communicating the potential impact of overall health may help reduce the discrepancy in postoperative satisfaction across ASA classifications.